Professional readiness of optant as a factor of existential selection - Yurchinska, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
In the article the empiric typology of personality is presented with the different structure of professional readiness in the situation of existential choice.